PERAN LINGKUNGAN SOSIAL DALAM KEPATUHAN PAJAK BUMI DAN BANGUNAN PEDESAAN DAN PERKOTAAN DI KOTA SERANG - Lestari, Ajeng; Ristiyana, Rida; Irawan, Dede (Jurnal Akuntansi Trisakti, 2026)
PBB-P2 taxpayer compliance is crucial as it significantly affects regional revenue used for local development. However, PBB-P2 revenue in Serang City is still far below the target. Factors that affect tax compliance include love of money, machiavellianism, nationalism, social environment. This study aims to examine the influence of love of money, machiavellianism, and nationalism with the social environment as a moderating variable on PBB-P2 taxpayer compliance in Taktakan District, Serang City. The use of the social environment as a moderating variable is a novelty of this research, which employs quantitative methods. This study used purposive sampling with 100 individual taxpayers PBB-P2 in Taktakan District, Serang City. Data were collected through a questionnaire and analyzed using SmartPLS 4.0. The results show that love of money and machiavellianism have a negative and significant influence on taxpayer compliance, while nationalism has a positive and significant influence on taxpayer compliance. The moderation test results show that the social environment strengthens the effect of nationalism on taxpayer compliance, but does not moderate the effects of love of money and machiavellianism. The findings strengthen the Theory of Planned Behavior, Attribution Theory which emphasizes that tax behavior is influenced by individual values and character. The social environment proved to be more effective at reinforcing nationalism than suppressing opportunistic impulses. Therefore, increasing compliance is not enough to improve systems and services, but it is necessary to pay attention to aspects of taxpayer behavior. The Serang City Bapenda needs to develop a management strategy to a more comprehensive approach.